FEASIBILITY OF THE CONSERVATIVE TREATMENT OF SPLENIC INJURIES IN BLUNT ABDOMINAL TRAUMA - M. M. Abakumov; I. E. Galankina; A. P. Vilk (Неотложная медицинская помощь, 2016)
ABSTRACT. In blunt trauma, the structural features of the splenic parenchyma usually predispose to a significant intra-abdominal bleeding, so the excision of the damaged spleen is considered a main treatment technique in a majority of cases. However, a number of recent clinical studies have proved the necessity of a differentiated approach to making the treatment decisions and demonstrated the possibility of spleen salvage in certain cases.The most debatable issue is the management tactics in splenic injury associated with the formation of subcapsular hematoma. It is necessary to emphasize that the conservative treatment of such splenic injury implies a persisting risk of double-stage splenic rupture with following intra-abdominal bleeding.The Sklifosovsky Research Institute traditionally deals with injury management in all aspects and has gained a wide experience in splenic injury treatment that makes possible to demonstrate the choice of treatment tactics with regard to the splenic injury severity, and patient’s condition. A conservative management of spleen injury is reasonable only in stable patients and requires an additional use of instrumental diagnostic techniques. Morphological studies suggest that reparation processes around the splenic hematoma arise early enough and proceed, as a rule, with no signs of a purulent inflammation.